(untitled) (Research, Society and Development, 2022)
The bioprospecting of secondary metabolites with antimicrobial action produced by filamentous fungi isolated from various ecosystems using agro-industrial residues is of considerable importance, since it reconciles the discovery of new antimicrobial agents with the reduction of environmental impacts adding economic value to wastes. The present paper investigated the potential of filamentous fungi for antimicrobial metabolites production using alternative media based on corn steep liquor, cassava wastewater and glycerol as substrates in different combinations. From 15 filamentous fungi assayed in preliminary screening, Paecilomyces variotii UCP 0334, Aspergillus flavus UCP 0316, Aspergillus foetidus UCP 0360, Aspergillus niger UCP 1064 e Aspergillus sp. 74M4 showed higher activity against all tested bacteria. After submerged fermentation in media containing corn steep liquor, cassava wastewater and glycerol, P. variotii UCP 0334 exhibitted greater activity and spectrum of action with inhibition halos ranging from 7 to 28 mm in diameter against all Gram negative and positive bacteria tested regardless of the culture medium type. It is worth mentioning that all fungi in alternative medium containing cassava wastewater and glycerol (CWWG) showed inhibitory activity against 3 bacteria with inhibition halos ranging from 9 to 15 mm. On the other hand, the medium containing corn steep liquor and glycerol (CSLG) favored higher biomass yield for all fungi. These results stimulate further studies of identification and characterization of the secondary metabolites produced by the selected fungi with a view to discovering new antimicrobial drugs.